Kinetics of Oxytocin Response to Repeated Restraint Stress and/or Chronic Cold Exposure - Danevova, V.; Kvetnansky, R.; Jezova, D. (Hormone and Metabolic Research, 2013)
Recently, several new atypical actions of circulating oxytocin are emerging, which may be of importance for the physiological effects of oxytocin released during stress. However, little information is available on oxytocin response to chronic stress stimuli. The aim of the present study is to deepen the knowledge on oxytocin secretion during chronic and repeated stress. The main hypothesis to be tested was that oxytocin release in response to single and to repeated or chronic stress is of different kinetics. Adult male Sprague-Dawley rats were exposed to 2 different stress stimuli or their combination. Restraint (immobilization) of different duration (10–120 min) and number of repetitions (1 or 7 times) as well as chronic exposure (28 days) to cold temperature were used. Concentrations of oxytocin in plasma and posterior pituitary were measured by a radioimmunoassay. Concentrations of oxytocin in plasma increased significantly in response to both single and repeated immobilization. Acute immobilization caused rapid increase already after 10 min of restraint, while the recovery occurred only after 24 h. Repeated restraint caused delayed onset of increased oxytocin release and a more rapid recovery to prestress levels after 3 h. In conclusion, the results of the present study show that though with a different kinetics, increased oxytocin release is preserved during repeated exposure to an intensive stressor, namely immobilization for 120 min. During repeated exposure to shorter stressors, an adaptation in oxytocin responses may occur. This should be taken into account with respect to cardiovascular and metabolic effects of stress-induced oxytocin.
Keywords: hormone; immobilization; ambient temperature